Modified Liquid-Based Cytology Technique for Immunocytochemistry in Effusion Specimen - Patarapadungkit, Natcha (Asian Pac J Cancer Prev, 2019)
OBJECTIVE: Immunocytochemistry (ICC) of serous effusion is an important tool for the diagnosis of benign and malignant cells. Our aim was to develop a modified liquid-based cytological technique for ICC (i.e., a modified LBC). METHODS: Serous effusions of 110 cases were collected for cytological examination: 50 were negative for malignancy albeit benign mesothelium was found, and 60 were confirmed metastatic adenocarcinoma according to the modified LBC preparation. The latter were stained for EMA, Ber-EP4, Calretinin, and p63 then interpreted by both a cytotechnologist and a pathologist. A comparative analysis of the diagnostic results was conducted. RESULTS: The results of the metastatic adenocarcinoma were 100% (60/60) positive for EMA and 91.7% (55/60) positive for Ber-Ep4 but negative for calretinin and p63. Cases negative for malignancy were 100% (50/50) positive for calretinin but negative for carcinoma markers. The difference between ‘positive for metastatic adenocarcinoma’ and ‘negative for malignancy’ in ICC was statistically significant (p < 0.001). CONCLUSION: The current study demonstrated that a panel marker, comprising EMA, Ber-EP4, and calretinin can be used for differentiating between cases of metastatic adenocarcinoma and benign mesothelium. The serous effusion specimen collected by the modified LBC technique is an effective preparation method for ICC.